Mobile Applications for Mental Health Providers. Issue 4 (1st October 2016) - Morganstein, Joshua
Abstract : Mobile devices such as smartphones and tablets have fundamentally changed the ways in which we interact with information. Far more than communication devices, smartphones and tablets are now indispensable tools in the pocket of healthcare providers. Mobile mental health applications (apps) provide instant access to up-to-date information on prevention, assessment and treatment. Self-help apps allow patients to take greater ownership of their own health and well-being. The past decade has seen an extraordinarily rapid proliferation of mobile medical apps. Though thousands of apps now exist, the challenge for healthcare providers and consumers alike has become sorting through mobile apps for those which provide accurate content delivered in the most user-friendly format. This article will review six mobile apps that can assist healthcare providers and consumers interested in enhancing mental health.